Characterization of few-layer graphene aerosols by laser-induced incandescence. (15th October 2020) - Musikhin, Stanislav; Fortugno, Paolo; Corbin, Joel C.; Smallwood, Greg J.; Dreier, Thomas; Daun, Kyle J.; Schulz, Christof
Abstract: Gas-phase synthesis is a promising route for producing large amounts of high quality few-layer graphene (FLG) nanoparticles economically, but optimizing these processes requires a detailed understanding of the formation kinetics, which in turn demands diagnostics for characterizing this material in situ . This work reports the first laser-induced incandescence measurements on FLG aerosols. Temporally- and spectrally-resolved incandescence signals from FLG particles are measured and used to calculate pyrometric temperatures. Differences between incandescence signals and pyrometric temperatures obtained from FLG and aerosolized soot nanoaggregates are attributed to the larger absorption cross-section and specific surface area of FLG compared to soot. LII signal intensity is found to vary linearly with particle number concentration measured independently by a condensation particle counter. Overall, these results demonstrate the potential for laser-induced incandescence to measure FLG nanoparticle mass (volume) fraction and active surface area in situ, as well as to differentiate graphene from other types of carbonaceous nanomaterials online. Graphical abstract: Image 1